HLA‐E allelic genotype correlates with HLA‐E plasma levels and predicts early progression in chronic lymphocytic leukemia. Issue 5 (2nd November 2016) - Wagner, Bettina; da Silva Nardi, Fabiola; Schramm, Sabine; Kraemer, Thomas; Celik, Alexander A.; Dürig, Jan; Horn, Peter A.; Dührsen, Ulrich; Nückel, Holger; Rebmann, Vera
Abstract : BACKGROUND: Human leukocyte antigen‐E (HLA‐E) is a nonclassical major histocompatibility complex class I molecule that recently came into sharper focus as a putative marker of advanced tumor stages and disease progression. In solid tumors, increased HLA‐E expression as well as elevated soluble HLA‐E (sHLA‐E) plasma levels are associated with a poor prognosis; however, a role for HLA‐E in hematologic malignancies remains to be established. METHODS: The authors analyzed HLA‐E alleles and sHLA‐E levels in a cohort of 110 individuals with chronic lymphocytic leukemia (CLL). RESULTS: In patients with CLL, levels of sHLA‐E increased with advanced disease stage ( P  = .01) and decreased after therapy ( P  = .01). Longitudinal follow‐up revealed that both HLA‐E *01:03 alleles and high levels of sHLA‐E were significantly associated with a requirement for early treatment in patients with CLL ( P  = .027 and P  = .023, respectively). In vitro, sHLA‐E inhibited degranulation and interferon‐γ production by natural killer (NK) cells when cocultivated with tumor cells. Moreover, sHLA‐E loaded onto microspheres induced transforming growth factor‐β release by NK cells. Multivariate analysis revealed that the presence of at least 1 HLA‐E *01:03 allele was an independent predictor of a requirement for early treatment. CONCLUSIONS: HLA‐E alleles and sHLA‐E levels may represent novel biomarkers for early disease progression in patients with CLL. Cancer 2017;123:814–23. © 2016 American Cancer Society . Abstract : In a cohort of 110 individuals with chronic lymphocytic leukemia, human leukocyte antigen‐E ( HLA‐E )*01:03 alleles and high levels of soluble HLA‐E are significantly associated with an early treatment requirement. HLA‐E alleles and soluble HLA‐E levels may represent novel biomarkers for early disease progression in patients with chronic lymphocytic leukemia.